Menstrual health and related problems in adolescent girls of Lucknow district: a cross sectional study - Singh, Geeta; Khanna, Anish; Agarwal, Monika; Singh, V. K.; Sachan, Rekha (International Journal Of Community Medicine And Public Health, 2018)
Background: Menstruation and related problems are difficult issues for adolescent girls and are a common reason for consulting healthcare providers. The objective of the study was to study the age of menarche, menstrual pattern, menstrual related health problems and health seeking behaviour for it. Methods: A cross sectional study was carried out in urban as well as rural schools of Lucknow district from August 2014 to September 2015. Multistage random sampling was used to select the requisite number of girls. A total of 600 girls of age group 10-19 years were interviewed and analysed using appropriate statistical methods Results: The mean age of menarche of the total population was 13.2±1 years. During menstruation, urban girls had significantly excessive passage of clots (26.5%) and faced more discomfort in their routine activities (78.8%) when compared to their rural counterpart (25.2% and 73.4% respectively), whereas the relation was inverse with regard to school absenteeism that was significantly higher in rural girls (44.0%) than urban girls (32.3%). The usual age of menarche as well as the pattern of pre-menstrual symptoms varied significantly between the girls of rural and urban areas. Conclusions: With few exceptions, menstrual health related problems have an unequal distribution in girls of rural and urban origin. Hence effective management of menstrual problems will lose its chase unless health education targeting all the three groups viz.; adolescent girls, concerned parents and teachers have to be uniformly strengthened.